2008
DOI: 10.1074/jbc.m709387200
|View full text |Cite
|
Sign up to set email alerts
|

Octaarginine- and Octalysine-modified Nanoparticles Have Different Modes of Endosomal Escape

Abstract: The present study examines the role of surface modification with an octaarginine peptide (R8) in liposomal escape from endocytic vesicles, using octalysine (K8) as a control cationic peptide; the mechanism of endosomal escape of liposomes was also investigated. Gene expression of condensed plasmid DNA encapsulated in R8-modified nanoparticles was more than 1 order of magnitude higher than that of K8-modified nanoparticles, and 2 orders of magnitude higher than gene expression using unmodified nanoparticles. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
158
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 185 publications
(168 citation statements)
references
References 53 publications
7
158
2
1
Order By: Relevance
“…(ii) the system delivers siRNA to the cytosol quite efficiently. Imaginig data revealed that most of the siRNAs were not colocalized in the lysosomal compartment (Fig.3), which is consistent with previous reports indicating that a high density of R8 peptide on the surface of nanoparticle facilitates the induction of macropinocytosis, which is an advantageous route for efficient intracellular trafficking, and which stimulates efficient endosomal escape (Khalil IA et al, 2006;El-Sayed A et al, 2008). (iii) there is no need to use chemically modified siRNA (Braasch DA et al, 2003) to protect against degradation in the serum because siRNA is efficiently encapsulated within a nanoparticle (Nakamura Y et al, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…(ii) the system delivers siRNA to the cytosol quite efficiently. Imaginig data revealed that most of the siRNAs were not colocalized in the lysosomal compartment (Fig.3), which is consistent with previous reports indicating that a high density of R8 peptide on the surface of nanoparticle facilitates the induction of macropinocytosis, which is an advantageous route for efficient intracellular trafficking, and which stimulates efficient endosomal escape (Khalil IA et al, 2006;El-Sayed A et al, 2008). (iii) there is no need to use chemically modified siRNA (Braasch DA et al, 2003) to protect against degradation in the serum because siRNA is efficiently encapsulated within a nanoparticle (Nakamura Y et al, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…It is assumed that endosomal escape would not be sufficient for achieving effective PC-SOD delivery. We recently reported that a liposome surface modification with the pH-sensitive fusogenic peptide, GALA, enhanced endosomal escape and permitted cytosolic delivery to be efficiently achieved [25,26,27]. Accordingly, it would be expected that the modification of GALA with R8-LP (PC-SOD) would show stronger anti-oxidant effects.…”
Section: Evaluation For Dismutation Activity Of R8-lp (Pc-sod)mentioning
confidence: 99%
“…It has been reported that high density R8-LP is taken up efficiently by cells via macropinocytosis [21]. Moreover, R8-LP, composed of DOPE and PA, can achieve efficient endosomal escape, thus enhancing cytoplasmic delivery [25]. We first checked the effect of PC-SOD on the liposome preparation (Fig S1 in Supplementary material).…”
Section: Preparation Of R8-lp (Pc-sod)mentioning
confidence: 99%
See 1 more Smart Citation
“…Particle diameters were around 150 nm and the ζ-potentials were around + 30 mV. The outer envelope of all carriers had a endosome-fusogenic composition [27]. For the DF-MITO-Porter, the inner envelope had a mitochondria-fusogenic composition [19], while a non-mitochondrial fusogenic composition [19] was used in the control inner envelope.…”
Section: Construction Of Df-mito-porter Encapsulating Dnase Imentioning
confidence: 99%